Development of a Project-Based Assessment Instrument for Critical Thinking and Patriotism Values in Elementary Schools - Muhamad Rifai; Ali Mustadi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Metro, 2026)
Conventional assessment practices in elementary schools often separate cognitive evaluation from character development, thereby limiting the measurement of students' competencies in a holistic manner. This study addresses the need for an authentic assessment instrument that integrates critical thinking skills and patriotism values within Pancasila Education. The study aimed to develop a project-based assessment instrument that is feasible, practical, and effective for fifth-grade students. Using the 4D Research and Development model (Define, Design, Develop, and Disseminate), the study involved validation by content and assessment experts, practicality questionnaires administered to teachers and students, and a quasi-experimental Nonequivalent Control Group Design. The participants consisted of fifth-grade students at SD N 1 Kadipiro, divided into an experimental group (n = 28) and a control group (n = 32), with a total of 60 participants. Data were analyzed using t-tests, N-gain analysis, and ANCOVA. The results indicated a high level of feasibility, with content expert validation reaching 90% and assessment expert validation reaching 97%. The instrument was also found to be highly practical based on user responses. ANCOVA results revealed significant differences between the experimental and control groups in terms of critical thinking skills (F(1, 57) = 196.13, p < 0.001) and patriotism values (F(1, 57) = 444.44, p < 0.001), with the experimental group demonstrating better outcomes than the control group. In conclusion, the developed project-based assessment instrument is feasible, practical, and highly effective, providing an innovative solution for implementing comprehensive and authentic assessment in elementary education.